Characterization of ceiling smoke temperature profile and maximum temperature rise induced by double fires in a natural ventilation tunnel. (February 2020) - Wang, Qiang; Wang, Shaoming; Liu, Huan; Shen, Jiaying; Shang, Fengju; Shi, Congling; Tang, Fei
Abstract: In this paper, the ceiling smoke temperature distribution characteristics maximum temperature rises induced by double fire sources in a natural ventilation tunnel were studied. Longitudinal ceiling smoke temperature distribution induced by double fire sources with different burner separation distances is correlated with an exponential decay law. The variation of longitudinal temperature decay coefficient K for different burner separation distances is found to decrease with the increase of burner separation distance. Then a model of K considering the burner separation distance and dimensionless heat release rate is developed. Comparison between the calculated ceiling smoke temperature profile with the proposed model and experimental data in both this work and those from previous work shows good agreement. Besides, the study also concerns the variation of maximum smoke temperature beneath the tunnel ceiling induced by double fire sources with different heat release rate and different burner separation distances. Under a certain heat release rate, the maximum temperature of the smoke beneath the tunnel ceiling decreases with increasing burner separation distances. A maximum temperature correlation, considering dimensionless heat release rates and the burner separation distances, is proposed. The calculated result show good agreement with the experimental data in this work and those from previous work. These new findings and models can provide a good reference for the design of tunnel fire safety.